SAR and molecular mechanism studies of monoamine oxidase inhibition by selected chalcone analogs - Raed Shalaby (3756112) (2019)
The present study describes the synthesis of a series of 22 chalcone analogs. These compounds were evaluated as potential human MAO-A and MAO-B inhibitors. The compounds showed varied selectivity against the two isoforms. The IC50 values were found to be in the micromolar to submicromolar range. The Ki values of compound 16 were determined to be 0.047 and 0.020 μM for the inhibition of MAO-A and MAO-B, respectively. Dialysis of enzyme-inhibitor mixtures indicated a reversible competitive mode of inhibition. Most of the synthesized chalcone analogs showed a better selectivity toward MAO-B. However, introducing of 2,4,6-trimethoxy substituents on ring B shifted the selectivity toward MAO-A. In addition, we investigated the molecular mechanism of MAO-B inhibition by selected chalcone analogs. Our results revealed that these selected chalcone analogs increased dopamine levels in the rat hepatoma (H4IIE) cells and decreased the relative mRNA expression of the MAO-B enzyme. Other Information Published in: Journal of Enzyme Inhibition and Medicinal Chemistry License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/14756366.2019.1593158